A new routing metric for DYMO protocol on mobile AD HOC network - Salleh, Noor Amani (2013)
Mobile ad hoc networks (MANETs) are consists of mobile devices connected wirelessly. MANETs communicate without any fixed infrastructure or any centralized domain. All the nodes are free to move randomly within the network and share information dynamically. Routing protocol in MANET show how the mobile nodes messages are forwarded in a multi-hop fashion. The wireless connectivity and node mobility in MANET networks contributes in rapid topological changes, which brings the need for a channel aware routing protocol. Hence, the need for efficient routing protocols to allow the nodes to communicate. In such a communication scheme a routing protocol play an important role in the network performances. Achieving high user data rates over multi-hop wireless paths is considered the ultimate goal for MANET. To overcome this problem, several important modifications to the routing protocol algorithms are then considered to operate better in networks. This research work proposed a SNR-based routing metric for Dynamic Mobile Ad hoc Network onDemand (DYMO) routing protocol. This paper starts by investigate and compare the performance among reactive routing protocols in MANET. Secondly, the DYMO protocol choose routes based on SNR metric are modeled as proposed the new routing metric. Simulations scenarios are used for the work of the research by develop the new routing metrics in DYMO protocol module in OMNET++. The results show that SNR-DYMO improves the performance of the MANET in terms of throughput and packet delivery ratio throughout all simulation scenarios.